Evaluation of the expression of p53, MDM2, and SUMO-1 in oral lichen planus - Oliveira Alves, Mg; Balducci, I.; Rodarte Carvalho, Y.; Cabral, Lag; Nunes, Fd; Almeida, Jd (Wiley, 2013)
Objective: The objective of this study was to compare the expression of proteins p53, MDM2, and SUMO-1 in oral lichen planus (OLP) lesions, epithelial dysplasia, and squamous cell carcinoma. Materials and Methods: The sample consisted of the following five groups of cheek mucosa lesions: normal mucosa (NM), inflammatory fibrous hyperplasia (IFH), lichen planus, epithelial dysplasia, and squamous cell carcinoma. The tissue samples were stained with hematoxylin-eosin and submitted to immunohistochemistry using anti-p53, anti-MDM2, and anti-SUMO-1 antibodies. Results: The results of this study demonstrated similar expression of p53 and MDM2 between OLP, oral epithelial dysplasia and, to a lesser extent, between OLP and oral squamous cell carcinoma (OSCC). However, for SUMO-1 a similar expression was observed in OLP, NM, and IFH. Conclusions: The results demonstrated overexpression of important proteins (p53 and MDM2) related to regulatory mechanisms of apoptosis in OLP, suggesting that there is a favorable environment for malignant transformation. The expression of SUMO-1 in OLP was similar to NM and IFH, suggesting that alterations of this protein occur at later stages of carcinogenesis, because important overexpression occurred in oral epithelial dysplasia and OSCC. © 2013 John Wiley & Sons A/S.
Keywords: Carcinoma; Immunohistochemical; Lichen planus; Proto-oncogene proteins c-mdm2; Squamous cell; SUMO-1 protein; Tumor suppressor protein p53